PELUANG PENGEMBANGAN PERIKANAN TANGKAP DI PROVINSI SUMATERA SELATAN - Septifitri Septifitri; Daniel R. Monintja; Sugeng Hari Wisudo; Sulaeman Martasuganda (Fakultas Perikanan dan Ilmu Kelautan, 2010)
South Sumatera province since 2000, began managing the fishery resources separately with the Province of Bangka Belitung. Bangka Belitung contribution in the fisheries sector of the South Sumatera province in 1999 by 72 %. Based on these conditions, then do research on fisheries development opportunities in the surrounding waters of South Sumatera. This research was conducted in February 2006 until July 2006 in two Regency namely Komiring Ogan Ilir and Banyuasin Regency. The results showed that the leading commodities in the province of South Sumatera is shrimp, crab, marine catfish (Arius thalassinus), and wolf herring (Chirosentrus dorab). This leading commodities still have a great opportunity to be developed for their utilization rates still ranged between 58,42% – 66,77% Fishing gear priority based on the analysis of MCA (multy Critical Analysis) with considering the biological aspects, technical, social and economic is trammelnet, drift gillnet and Stationary-bamboo lift net.